BUSINESS COMBINATIONS–A CASE STUDY. - Sapienza, Samuel R. (The Accounting Review, 1963)
This paper deals particularly with the acquisitiveness of one corporation, the bitumen-based products developer Flintkote Co. Flintkote was chosen because its history, especially the last four years, shows rapid change with numerous business combinations. These business combinations illustrate clearly the application of the accounting procedures of "pooling" and "purchasing" and offer an opportunity to study the effects arising from their use. The fact that accounts are stated in consolidation on a pooled or purchased basis is usually put into the first footnote to the consolidated balance sheet under a statement of consolidating principles. Flintkote has been an active company in the use of the pooling and purchasing concepts in business combinations. A business combination involves the mutual transfer of rights by stockholders of one corporation with those of another corporation. The accounting profession attempts to give reasonable expression to what has occurred. In this article the author comments on various aspects of the accounting principles pooling and purchasing.